Etyka utylitarystyczna Petera Singera – szanse i możliwości przekształcenia praw zwierząt - Dłużewicz, Alicja (ETHICS IN PROGRESS, 2014)
This article is an attempt to redefine and extend basic terms of law, such as “person” or “justice,” to include self-conscious, non-human animals in the moral community. This need arises due to the evolution of our moral thinking, which is related to the process of recognition. Support for animals coming under the protection of law can be provided by Peter Singer's utilitarian ethics, which shows the importance of respecting other’s interests and giving them the possibility of living under decent conditions.